Problematics Of The Legal Position Of Gender In The Division Of Nafkah After Divorce (Case Study In Cirebon City) - Nurkholis; Abdul Aziz; H. E. Sugianto (JURNAL ILMU SYARIAH, 2025)
The issue of gender inequality in the legal framework governing post-divorce maintenance in Cirebon City continues to face significant challenges in its implementation. Although regulations such as Marriage Law No. 1 of 1974, Law No. 16 of 2019, and the Compilation of Islamic Law (KHI) establish the obligation of financial support for former wives and children, practical application reveals considerable disparities. Women who file for divorce (cerai gugat) encounter greater difficulties in securing financial maintenance compared to those in divorce initiated by the husband (cerai talak), where maintenance is automatically granted through an ex officio court ruling. Beyond regulatory issues, social, economic, and patriarchal cultural factors further exacerbate the difficulties faced by women after divorce. Strong societal norms discourage women from demanding financial support due to family pressure and social stigma. Even when courts grant maintenance, low compliance rates among ex-husbands and weak enforcement mechanisms pose major obstacles to ensuring economic rights for divorced women. The need for inclusive legal reforms and increased legal awareness is essential to safeguard women’s rights. Updates to regulations and improvements in enforcement mechanisms are required to ensure that divorced women receive fair financial support without structural barriers. With more effective policies and heightened legal awareness, gender disparities in post-divorce financial distribution can be minimized, providing better legal protection for women facing divorce. Keywords: Post-divorce maintenance; gender justice; Islamic law; legal enforcement; women's rights.